Solar energy potential in horn of Africa: A comparative study using matlab/simulink - DURSUN, ERKAN (My University, 2021)
Geographically, the Horn of Africa is one of the regions that the Equator passes over, providing the opportunity for vigorous solar energy. However, despite the enormous solar energy resources, more than half of the region, 132 million populations have not yet access to electricity. This study presents an overview of the potential of solar energy in the region. Then review the current solar energy status and policies related to it. A Matlab/Simulink model is developed to show the comparative analyses of the solar radiation graphically on the photovoltaic modules and electricity outputs for the Horn of African countries' capitals. As a result of the simulation model, Ethiopia-Addis Ababa receives the highest annual solar radiation of 2915.03 kWh/m2 -year while Eritrea-Asmara with the lowest annual solar radiation of 2198.47 kWh/m2 -year. The annual electrical output of the photovoltaic modules in Ethiopia-Addis Ababa is the highest with 286.685 kWh/year and Eritrea-Asmara 216.214 kWh/year as the lowest in the region. The number of photovoltaic modules and the optimum tilt angles are calculated. For Ethiopia-Addis Ababa, the lowest photovoltaic module number is 10, and the optimum PV tilt angle is 11.163°. For Eritrea-Asmara, the highest photovoltaic module number is 14, with a tilt angle of 15.397
Keywords: The Horn of Africa; solar energy; Matlab